Gender mainstreaming in media and journalism education – an audit of media departments in Uganda, Rwanda and Ethiopia. (1st September 2016) - Dralega, Carol Azungi; Jemaneh, Agaredech; Jjuko, Margaret; Kantono, Rehema
Gender mainstreaming (GM) within media and journalism education and practice has been described by several scholars as good, representative, critical, ethical, just and balanced journalism. This article presents findings of a study exploring the extent of GM in media and journalism in university departments in Uganda, Rwanda and Ethiopia. Drawing on qualitative research approaches, the study found minimal, unclear and uncoordinated GM activities within most departmental policies, curricula, assessment and research. Whereas some respondents attributed this to the lack of teaching resources, others pointed to the lack of policy guidance and 'know-how' as well as a commitment to implement existing policies. There were also attitudinal standpoints dismissive of the significance of GM, posing concerns about perpetuating the hegemony of patriarchy already witnessed in journalism practice today. The findings underscore the need to revisit not just the policies and pedagogical approaches but also a focus on awareness- and knowledge-building especially among the teaching staff.